Gas Adsorption and Luminescent Properties of a Porous pcu-Type Zn(II) Coordination Polymer. Issue 12 (1st December 2016) - An, Zhe; Wang, Jian
Abstract : A new Zn(II) compound, namely {Zn2 (tdc)2 (pi)}n (1 H2 tdc = 2, 5-thiophenedicarboxylic acid, pi = piperazine), has been synthesized via the solvothermal reactions of Zn(NO3 )2 ·6H2 O, H2 tdc and pi. Single-crystal X-ray analysis reveals that compound 1 crystallizes in orthorhombic P nma space group with cell parameters a = 20.734(6), b = 20.994(6), c = 18.539(6), and β = 90. The title compound features a three-dimensional (3D) pillar-layered framework. The gas adsorption and luminescent properties of1 were investigated in the solid state at room temperature.